The Influence of Co-Precipitation Technique on the Structure, Morphology and Dual-Modal Proton Relaxivity of GdFeO3 Nanoparticles - Yamen Albadi; Maria S. Ivanova; Leonid Y. Grunin; Kirill D. Martinson; Maria I. Chebanenko; Svetlana G. Izotova; Vladimir N. Nevedomskiy; Rufat S. Abiev; Vadim I. Popkov (Inorganics, 2021)
Nanocrystals of gadolinium orthoferrite (GdFeO3) with morphology close to isometric and superparamagnetic behavior were successfully synthesized using direct, reverse and microreactor co-precipitation of gadolinium and iron(III) hydroxides with their subsequent heat treatment in the air. The obtained samples were investigated by PXRD, FTIR, low-temperature nitrogen adsorption-desorption measurements, HRTEM, SAED, DRS and vibration magnetometry. According to the X-ray diffraction patterns, the GdFeO3 nanocrystals obtained using direct co-precipitation have the smallest average size, while the GdFeO3 nanocrystals obtained using reverse and microreactor co-precipitation have approximately the same average size. It was shown that the characteristic particle size values are much larger than the corresponding values of the average crystallite size, which indicates the aggregation of the obtained GdFeO3 nanocrystals. The GdFeO3 nanocrystals obtained using direct co-precipitation aggregate more than the GdFeO3 nanocrystals obtained using reverse co-precipitation, which, in turn, tend to aggregate more strongly than the GdFeO3 nanocrystals obtained using microreactor co-precipitation. The bandgap of the obtained GdFeO3 nanocrystals decreases with decreasing crystallite size, which is apparently due to their aggregation. The colloidal solutions of the obtained GdFeO3 nanocrystals with different concentrations were investigated by 1H NMR to measure the T1 and T2 relaxation times. Based on the obtained r2/r1 ratios, the GdFeO3 nanocrystals obtained using microreactor, direct and reverse co-precipitation may be classified as T1, T2 and T1–T2 dual-modal MRI contrast agents, respectively.